MODEL GUERILLA MARKETING MUTU DALAM STRATEGI BRANDING KEUNGGULAN KHAS PESANTREN SALAF DALAM MENGHADAPI PERSAINGAN - Budi Santoso; Siti Aimah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze and formulate the Quality Guerilla Marketing Model as a branding strategy for the distinctive advantages of salaf Islamic boarding schools in facing competition with formal educational institutions. This research is motivated by the challenges of salaf Islamic boarding schools in communicating their substantive quality in the midst of the dominance of educational institutions that rely on formal promotion and modernization of the system. The research uses a qualitative approach with the type of case study carried out at the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Bangorejo Banyuwangi. Data collection techniques include in-depth interviews, participant observations, and documentation studies, while data analysis is carried out using the Miles and Huberman interactive model with data validity checks through triangulation of sources and techniques. The results of the study show that the branding of salaf pesantren is built through substantive qualities that are alive in daily educational practices, strong cultural relations, and the authority of kiai as the main social legitimacy. In addition, pesantren implement selective adaptation to modern technology and systems as a competitiveness strategy without eliminating the identity of the salaf.